Karakteristik Durian Lokal Sinapeul di Dusun Sinapeul Kecamatan Ujungberung, Majalengka - Adhya, Ilham; Hendrayana, Yayan; Supartono, Toto; Herlina, Nina; Kosasih, Dede; Nasihin, Iing; Nurdin, Nurdin; Chandra, Rufidi; Kristanto, Martinus Ari; Suswanto, Suswanto (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2024)
Durian (Durio spp.) is a tropical fruit with high economic and cultural value in Indonesia. As a member of the genus Durio, there are nine consumable species of durian, with D. zibethinus being the most widely cultivated. Indonesia boasts various types of durian, differing in taste, aroma, and flesh color, which are crucial assets for increasing the number of superior parent plants. Durian is renowned for its unique taste and offers numerous benefits, including consumption as fresh or processed fruit, use in anti-aging treatments, and blood pressure improvement. Morphological identification of durian is essential for determining fruit quality, which is vital in plant breeding. The Sinapeul durian, a local variety from Majalengka, has unique characteristics and significant economic value, but knowledge about its distribution remains limited. This research aims to analyze the distribution and characteristics of the Sinapeul durian around the area of PT. Indocement Tunggal Prakarsa Tbk Unit Palimanan Cirebon, to support conservation and sustainable utilization efforts, and to provide a basis for the propagation of the increasingly rare Sinapeul durian